Behavioural and physiological effects of oral midazolam premedication in paediatric dental general anaesthesia: a pilot study - Badrul Hisham, Abdul Rauf; Mamat, Noraida; Ismail, Ahmad Faisal; Wan Ahmad, Wan Muhamad Amir; Samsudin, Norsamsu Arni (CJERT Publications, 2023)
Children undergoing anesthesia, including dental treatment under general anesthesia (DGA), tend to develop severe preoperative anxiety. Oral Midazolam is one of the many premedications used in controlling behavior and reducing anxiety in children before general anesthesia. This study is aimed to evaluate the effect of oral midazolam premedication on recovery behavior and physiologic effects of children undergoing DGA. It involved thirty uncooperative children aged from 2 to 11 years old. Group I (n = 15): children received 0.5 mg/kg midazolam orally, while Group II (n = 15): children who did not receive any premedication. Their peripheral capillary oxygen saturation, respiratory rate, and heart rate were measured upon arrival at the post-anesthesia care unit. The recovery behavior was evaluated using the Modified Houpt Behavior Rating Scale. Fisher's Exact test and Mann-Whitney test were used for data analysis. There are no significant differences in both groups' post-behavior and physiologic parameters (p>0.05). However, children in Group II reported tachycardia (13.3%, n= 2), hypoxemia (13.3%, n= 2), and bradypnea (13.3%, n= 2), compared to one case of bradypnea (6.7%) in Group I at 30 minutes. Although there were no significant differences between both groups (p>0.05), Group I showed less movement and no crying reaction but was more awake—no significant association of premedication oral midazolam with successful recovery behavior (p=0.381). One child in Group II had an episode of vomiting. An interesting pattern of improved recovery behavior and physiology was identified among children receiving oral midazolam premedication. More research with a bigger sample size is needed to investigate the effect of oral Midazolam in pediatric DGA and to determine the optimal effect of premedication.